PENGARUH E-SERVICE QUALITY TERHADAP MINAT BELI PRODUK FASHION DI SHOPEE (Studi kasus konsumen Toko Adilla.Id) - Nurul Fitri Habibah; Nur Fikriyah (Journal Of Business, Finance, and Economics (JBFE), 2022)
E-service quality is a service provided to consumers networked on the internet, as a method of expanding the expertise of an application to facilitate buying and selling activities and distribution efficiently. The research method used is a quantitative method which can be interpreted as a research method based on the philosophy of positivism, used to examine certain populations or samples. The results of the analysis show that there is a positive and significant influence between E-service quality on purchase intention. From the simple regression analysis test it is known that the calculated F value = 14,291 with a significance level of 0.000 <0.05, so the regression model can be used to predict the e-service quality variable or in other words there is an effect of the e-service quality variable (X) on the variable buying interest (Y). Test R Square (R2) or the quadratic of the value of R, which shows the coefficient of determination. This figure will be converted into a percentage, which means the percentage of the influence of the e-service quality variable on the purchase intention variable. The R2 value of 0.198 means that the percentage contribution of e-service quality to purchase intention is 19.8%, while the rest is influenced by other variables not included in this model. This figure (19.8%) is significant even though it is not as perfect as 100% in the point of influence.